Characterization and distribution of Pasteurella species recovered from infected humans. - Holst, E (1992)
During a 3-year period, all Pasteurella strains recovered at the Clinical Microbiological Laboratory, Lund, Sweden, were studied biochemically with respect to their relationship to the recently described taxa of this genus. Of 159 strains recovered from 146 infected humans, 95 were identified as Pasteurella multocida subsp. multocida, 21 as Pasteurella multocida subsp. septica, 28 as Pasteurella canis, 10 as Pasteurella stomatis, and 5 as Pasteurella dagmatis. The homology within and between the Pasteurella species regarding cellular fatty acids and enzymatic activities was also studied. Strains of the different Pasteurella species were indistinguishable from each other regarding fatty acid composition; all strains contained major amounts of C14:0, C16:1, C16:0, and 3-OH-C14:0 acids and minor amounts of C18:2, C18:1, and C18:0 acids. Neither did the enzymatic activities distinguish between strains belonging to different species. In addition, of 56 strains examined, toxin production was demonstrated only in 1 strain each of P. multocida subsp. multocida and P. canis. Except for one severe case of necrotizing cellulitis involving P. dagmatis, P. multocida subsp. multocida or P. multocida subsp. septica was recovered in the more serious cases of infection. Except for P. canis, which in all cases was associated with dog bites, most Pasteurella strains were recovered in cases of infection associated with cat bites or scratches. Pasteurella strains occurred in four infected patients without evident connections with animals.